Characterization and expression of human bifunctional 3'-phosphoadenosine 5'-phosphosulphate synthase isoforms. - Fuda, Hirotoshi (2002)
Sulphonation, a fundamental process essential for normal growth and development, requires the sulphonate donor molecule 3'-phosphoadenosine 5'-phosphosulphate (PAPS), which is produced from ATP and inorganic sulphate by the bifunctional enzyme PAPS synthase. In humans, two genes encode isoenzymes that are 77% identical at the amino acid level, and alternative splicing creates two subtypes of PAPS synthase 2. The question as to whether distinctions in amino acid composition are reflected in differences in activity has been examined. The specific activity of the PAPS synthase 2 subtypes is 10- to 15-fold higher than that for PAPS synthase 1. The greater catalytic efficiency of the PAPS synthase 2 subtypes is demonstrated further by the 3- to 6-fold higher k(cat)/K(m) ratios for ATP and inorganic sulphate as compared with the ratios for PAPS synthase 1. In humans, PAPS synthase 1 is expressed ubiquitously, and is the dominant isoform in most tissues, whereas expression of the PAPS synthase 2 subtypes is variable and tissue-specific. It is noteworthy that, similar to other human tissues, PAPS synthase 1 also appears to be the dominant isoform expressed in cartilage. The latter finding initially created a conundrum, since there is a specific human dwarfing disorder that is known to be caused by a mutation in the PAPS synthase 2 gene. This apparent enigma would seem to be resolved by examination of cartilage from guinea-pigs as an animal model. Similar to humans, cartilage from mature animals predominantly expresses PAPS synthase 1. In contrast, expression of PAPS synthase 1 is relatively low in the cartilage of immature guinea-pigs, including the growth plate of long bones, whereas PAPS synthase 2 is the highly expressed isoenzyme.